WiMax crash course(photocopy) - Shepard Steven (McGraw-Hill, 2006)
* Introduction to Wireless and WiMAX * WiMAX History and Support Organizations * How WiMAX Works * WiMAX Applications and Services * WiMAX Regulatory Issues * WiMAX and Other Broadband Wireless Features